Vulvar leiomyoma in a postmenopausal woman mimicking common labial swelling: a rare case report - Gupta, Tuhina; Singh, Bharti; Puri, Manju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Vulvar leiomyoma is a rare benign smooth muscle tumor that accounts for a very small proportion of gynecological and vulvar neoplasms and is often misdiagnosed as more common vulvar swellings such as Bartholin gland cysts. We report a case of a 58-year-old multiparous postmenopausal woman who presented with a painless, slow-growing vulvar mass of 10 years’ duration. Clinical examination revealed a well-circumscribed, firm, non-tender mass involving the right labia majora. The patient underwent complete surgical excision of the lesion. Histopathological examination confirmed the diagnosis of vulvar leiomyoma. The postoperative course was uneventful, with no evidence of recurrence on follow-up. This case highlights the importance of considering vulvar leiomyoma in the differential diagnosis of long-standing labial swellings, particularly in peri- and postmenopausal women. Complete surgical excision remains the treatment of choice and provides both definitive diagnosis and excellent prognosis.